Pancreatic Alpha Cell Mass Across Adult Human Lifespan - Moin, Abu Saleh Md (Eur J Endocrinol, 2019)
AIM: To establish pancreatic alpha-cell mass in lean non-diabetic humans over the adult lifespan, performed as a follow up study to beta cell mass across the adult human lifespan. METHODS: We examined human pancreatic autopsy tissue from 66 lean non-diabetic individuals aged from 30–102 years, grouped into deciles: 3(rd)(30-39 years), 4(th)(40-49 years), 5(th)(50-59 years), 6(th)(60-69 years), 7(th)(70-79 years), 8(th)(80-89 years) and 9(th) deciles(90+ years). Sections of pancreas were immunostained for glucagon and analyzed for fractional alpha-cell area. Population-based pancreatic volume data was used to calculate alpha-cell mass. RESULTS: With advanced age, the exocrine pancreas undergoes atrophy demonstrated by increased fat area (as % exocrine area) (0.05±0.01 vs 1.6±0.7% fat area of total exocrine pancreas, 3(rd) vs 9(th) decile, p<0.05). Consequently, islet density increases with age (2.7±0.4 vs 10.5±3.3 islets/mm(2), 3(rd) vs 9(th) decile, p<0.05). Alpha-cell fractional area increases with advanced age (0.34±0.05% vs 0.73±0.26%, 3(rd) vs 9(th) decile, p<0.05). However, alpha-cell mass remains constant at ~190mg throughout the adult lifespan in lean non-diabetic humans. Within islets, alpha-cell distribution between mantle and core is unchanged across deciles (1862±220 vs 1945±200 vs 1948±139 alpha-cells in islet mantle/mm(2), 3(rd) vs 6(th) vs 9(th) decile, p=0.93 and 1912±442 vs 1449±123 vs 1514±168 alpha-cells in islet core/mm(2), 3(rd) vs 6(th) vs 9(th) decile, p=0.47), suggesting that human islets retain their structural organization in the setting of age-related exocrine atrophy. CONCLUSIONS: Consistent with our previous findings for beta-cell mass, alpha-cell mass remains constant in humans, even with advanced age. Pancreatic endocrine cells are much more robustly preserved than exocrine cells in aged humans and islets maintain their structural integrity throughout life.